Taxonomia e biodiversidade de parasitos branquiais de Schizodon borellii (Osteichthyes, Anostomidae) coletados na planície de inundação do alto rio Paraná, antes e após a construção da Usina Hidrelétrica de Porto Primavera, Brasil. - Evangelista, Caroline Longhini (2013)
Brazil is a privileged country in water resources, having a land area exceeding 8,000,000 square kilometers, with about 20% of global freshwater and housing the richest and most diverse fish fauna of the world. These animals are more parasites in vertebrates because of the peculiarities existing in the aquatic environment that facilitates access and penetration of these pathogens. The parasite usually occurs as a result of an imbalance between the environment, the host and the parasite. The groups of parasites most commonly used in the study of environmental stress impacts caused by dam construction and pollution are ectoparasites, especially monogeneans, mostly found in the gills and integument. In São Paulo, Sérgio Motta Hydroelectric Engineering, also known as the Porto Primavera Dam, after its construction (1980-1998) caused significant changes in the hydrological regime of the downstream floodplain of the upper Paraná River and consequently changed the whole dynamic present this ecosystem, whose impacts are often unknown. This study used ectoparasite fauna of the plain Schizodon borellii to evaluate the effects of the construction of this dam these helminths. We recorded ten species of monogeneans, five considered new species to science. Furthermore, it was demonstrated decrease in the population of parasites with significant change in the average intensity of the specimens between the two periods. These results can be explained by the alterations downstream of the Paraná River after dam construction, changing its temperature, pH, phosphorus, potassium and other limnological aspects. These impacts could explain the observed change in the fauna of parasites.